2016
DOI: 10.1021/acs.energyfuels.5b02292
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Polyaromatic Hydrocarbon (PAH) Molecular Coverage during Fossil Oil Analysis by Combining Gas Chromatography and Atmospheric-Pressure Laser Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS)

Abstract: Thousands of chemically distinct compounds are encountered in fossil oil samples that require rapid screening and accurate identification. In the present paper, we show for the first time, the advantages of gas chromatography (GC) separation in combination with atmospheric-pressure laser ionization (APLI) and ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) for the screening of polyaromatic hydrocarbons (PAHs) in fossil oils. In particular, reference standards of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 71 publications
3
65
0
Order By: Relevance
“…The above mentioned problems can now be overcome with the coupling of a gas chromatograph to an ultra‐high resolving mass spectrometer. Recently, the combination of GC and APLI has been successfully used for the analysis of polyaromatic hydrocarbons (PAHs) in fossil oil samples . Features such as sensitivity, high mass accuracy and high resolution can now be combined to a powerful chromatographic separation, enabling a deeper understanding of the samples on a molecular level …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above mentioned problems can now be overcome with the coupling of a gas chromatograph to an ultra‐high resolving mass spectrometer. Recently, the combination of GC and APLI has been successfully used for the analysis of polyaromatic hydrocarbons (PAHs) in fossil oil samples . Features such as sensitivity, high mass accuracy and high resolution can now be combined to a powerful chromatographic separation, enabling a deeper understanding of the samples on a molecular level …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the combination of GC and APLI has been successfully used for the analysis of polyaromatic hydrocarbons (PAHs) in fossil oil samples. 28 Features such as sensitivity, high mass accuracy and high resolution can now be combined to a powerful chromatographic separation, enabling a deeper understanding of the samples on a molecular level. 29 This work illustrates the analytical performance of the newly developed GC Orbitrap-based mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…Using GC/MS, Czechowski et al reported the distributions of n ‐alkanes from two brown coals with chain lengths ranging from C 12 to C 35 . The analysis of multiple polyaromatic hydrocarbons in fossil oil using GC/Fourier transform ion cyclotron resonance MS resulted in a high sensitivity …”
Section: Introductionmentioning
confidence: 99%
“…23 The analysis of multiple polyaromatic hydrocarbons in fossil oil using GC/Fourier transform ion cyclotron resonance MS resulted in a high sensitivity. 24 With the development of MS techniques, tandem MS (MS/MS) has been applied to minimize signal interferences in complicated samples, which can improve the sensitivity and increase the qualitative ability in monitoring coal conversions. 25,26 Gas chromatography/ quadrupole time-of-flight MS (GC/Q-TOF MS) has proven to be an effective approach for understanding the molecular compositions of unknown complexes.…”
mentioning
confidence: 99%
“…59, 60, 6569 However, the biggest challenge in the coupling of liquid and gas chromatography is that it limits the FT-ICR MS analysis time, and thus the ability to better separate isobaric species, due to the slow acquisition rates needed for ultrahigh resolution mass acquisitions. 48, 65 Alternatively, other post-ionization, gas-phase separations have been proven to be a better match for FT-ICR MS analysis. 7079 In particular, ion mobility spectrometry (IMS) presents many advantages for the analysis of complex mixtures, providing orthogonal separation to FT-ICR MS that is based on the tri-dimensional structure of the molecule.…”
Section: Introductionmentioning
confidence: 99%